Pengaruh Model Pembelajaran Inkuiri Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPAS Materi Gerhana di Kelas VI SD Negeri 060900 Tapian Nauli - Lubis, Aulia Chairani; Mujib, Abdul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
The purpose of this study was to analyze the effect of the inquiry learning model on students’ learning outcomes in IPAS on the topic of eclipses in Grade VI at SD Negeri 060900 Tapian Nauli. This study employed a quantitative approach using a quasi-experimental method to examine the impact of a specific instructional treatment on one group compared to another group that received a different treatment. The research design used was the Posttest-Only Control Group Design. The population of this study consisted of all Grade VI students at SD Negeri 060900 Tapian Nauli, totaling 52 students. The sample in this study consisted of students from classes VI-A and VI-B who were selected using purposive sampling. The findings indicated that the inquiry learning model had a positive effect on students’ learning outcomes related to eclipses. Students in the experimental group who were taught using the inquiry learning model achieved higher posttest scores than those in the control group who were taught using the conventional (lecture-based) method. Furthermore, the significance value obtained from the Independent Samples t-test was less than 0.05, indicating that H₀ was rejected and Hₐ was accepted. Therefore, it was concluded that the inquiry learning model had a significant effect on the IPAS learning outcomes of Grade VI students at SD Negeri 060900 Tapian Nauli.